(untitled) (Perspectivas em Ciência da Informação, 2008)
The increase in production in 20 Brazilian periodicals in Archive Science, Library and Information Science and Documentation is described (1972 to 2006). A total of 3,706 bibliographic records were examined. Tables and figures are presented, related to total number of published articles, total number of multiple authorship (co-authorship) articles, total number of periodical titles, and average number of articles per periodical. Final results show the 6 the average yearly production of 175 articles (2000 to 2006); the average yearly productivity being of 16 articles/year/periodical (2000 to 2006); the percentage for articles in co-authorship is 49.16%, close to the average percentage of single authorship articles, of 50.84% in 2006, and 85% of co-authorships coming from articles with two or three authors (1972 to 2006). In conclusion, few questions are discussed on the eventual causes of these results.